Association between herpes simplex virus type 1 and the risk of Alzheimer’s disease: a retrospective case–control study - Christine Johnston; Simon P Fletcher; Yunhao Liu; Shahed Iqbal; Nadine Jarousse (BMJ Open)
Objective A growing body of evidence points to a role for herpesviruses in the development of Alzheimer’s disease (AD) and a reduced risk of AD among patients receiving antiherpetic medications. We investigated the association between herpes simplex virus type 1 (HSV-1) and AD using real-world data (RWD) from USA.Design In a matched case–control study, patients with AD aged ≥50 years diagnosed between 2006 and 2021 were identified from the IQVIA PharMetrics Plus claims database. Controls were matched in a 1:1 ratio with subjects with AD on age, sex, region, database entry year and healthcare visit numbers.Results The study included 344 628 AD case–control pairs. History of HSV-1 diagnosis was present in 1507 (0.44%) patients with AD compared with 823 (0.24%) controls. HSV-1 diagnosis was found to be associated with AD (adjusted OR 1.80; 95% CI 1.65 to 1.96). Patients with HSV-1 who used antiherpetics were less likely to develop AD compared with those who did not use antiherpetics (adjusted HR 0.83, 95% CI 0.74 to 0.92).Conclusions Findings from this large RWD study implicate HSV-1 in the development of AD and highlight antiherpetic therapies as potentially protective for AD and related dementia.